Nilai Kebijaksanan Resi Gotama Dalam Serat Lokapala Sebagai Etika Resolusi Konflik Perang Saudara dalam Perebutan Hak Waris - Nabila Oktavia; Ila Maria Siti Nurfarida (Jurnal Online Baradha, 2026)
The widespread conflicts over inheritance rights in Indonesian society reflect a crisis of values within modern family life as well as a lack of ethical approaches used in resolving such disputes. This study aims to reveal the representation of the wisdom values of the figure Resi Gotama in Serat Lokapala as an ethical framework for conflict resolution among siblings in the context of inheritance disputes. The focus of the study is directed at how the teachings of Resi Gotama reflect spiritual values that can be transformed into guidelines for resolving family conflicts in the present day. This research employs a qualitative method with Lucien Goldmann’s genetic structuralism approach. The research steps include a literature study of the Serat Lokapala text, philological analysis of selected pupuh (metrical verses), and thematic interpretation of key values such as sumarah (submission/acceptance), darma (moral obligation), compassion, and ruwatan (spiritual liberation). The results indicate that the wisdom values of Resi Gotama reflect the cosmological and religious worldview of Javanese society, where conflict resolution prioritizes inner calm, spirituality, and deliberation rather than confrontation. The conclusion of this study is that the teachings of Resi Gotama can serve as a morally and socially relevant model for resolving inheritance conflicts in the modern era, while also making a tangible contribution to preserving local ethical values through the reinterpretation of classical Javanese literature. Key Words: Inheritance conflict, Wisdom values, Resi Gotama, Family conflict resolution, Spiritual values